2022
DOI: 10.3389/fgene.2022.955424
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis analysis of necroptosis-related genes in colorectal cancer based on bioinformatic analysis

Abstract: Background: Colorectal cancer (CRC) is one gastrointestinal malignancy, accounting for 10% of cancer diagnoses and cancer-related deaths worldwide each year. Therefore, it is urgent to identify genes involved in CRC predicting the prognosis.Methods: CRC’s data were acquired from the Gene Expression Omnibus (GEO) database (GSE39582 and GSE41258 datasets) and The Cancer Genome Atlas (TCGA) database. The differentially expressed necroptosis-related genes (DENRGs) were sorted out between tumor and normal tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“… 10 , 41 It has been reported that m6A plays an increasingly important role in various physiological and pathological processes in various cancers, 42 including pancreatic cancer, 43 breast cancer, 44 and our published CRC study. 45 While the roles of various programmed cell death (PCD) modes in CRC prognosis have been explored in the literature, these models have primarily focused on individual modes of cell death, such as the apoptosis-related prognostic signature, 46 autophagy-related signature, 47 , 48 , 49 , 50 , 51 cuproptosis-related signature, 52 , 53 , 54 ferroptosis-related signature, 55 , 56 , 57 necroptosis-related signature, 58 , 59 and pyroptosis-related prognostic signature. 60 , 61 , 62 , 63 , 64 , 65 However, the interplay between m6A modification and PCD in CRC prognosis remains unexplored, representing a gap in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 41 It has been reported that m6A plays an increasingly important role in various physiological and pathological processes in various cancers, 42 including pancreatic cancer, 43 breast cancer, 44 and our published CRC study. 45 While the roles of various programmed cell death (PCD) modes in CRC prognosis have been explored in the literature, these models have primarily focused on individual modes of cell death, such as the apoptosis-related prognostic signature, 46 autophagy-related signature, 47 , 48 , 49 , 50 , 51 cuproptosis-related signature, 52 , 53 , 54 ferroptosis-related signature, 55 , 56 , 57 necroptosis-related signature, 58 , 59 and pyroptosis-related prognostic signature. 60 , 61 , 62 , 63 , 64 , 65 However, the interplay between m6A modification and PCD in CRC prognosis remains unexplored, representing a gap in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…html). Furthermore, the "clusterProfiler", "org.Hs.eg.db", "enrichplot", "DOSE", and "ggplot2" packages in R language were employed for conducting GO and KEGG pathway analysis [13,14].…”
Section: Methodsmentioning
confidence: 99%